(untitled) (Journal of Contemporary Philology, 2021)
Every field research and every research approach, without exception, brings a series of challenges for both the researcher and the researched participants. Since the beginning of field research, researchers have faced multiple responsibilities towards the research environment, the research participants, the research community they belong to, and themselves. In this context, the question of research ethics arises. It means that the research does not cause any (intentional or unintentional) harm as a consequence, and researchers are expected to understand and respect the researched individuals or social groups. This paper aims to present the ethical aspects and problems researchers face in linguistic field research while paying particular attention to this issue in the Macedonian language. Considering that the methods and principles of fieldwork used in language studies are very similar to fieldwork methods in most humanities, this study also addresses the ethical aspects common to these scientific fields. A fundamental principle of research ethics is to ensure that respondent enters any research consciously and voluntarily. Obtaining consent should be a process of establishing and maintaining mutual trust between the respondent and the researcher.